THE INFLUENCE OF DIET ON ANEMIA SYMPTOMS IN ADOLESCENT WOMEN IN CLASS X SMA N 1 LIRIK - Sulastri, Ratih; Anggreni, Elsie; Bahriyah, Fitriyani; Guriti, Guriti; Susilawati, Budi (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2024)
Puberty in teenage girls is characterized by the occurrence of menstruation. The amount of iron lost during menstruation causes teenage girls at puberty to be at risk of anemia. The purpose of this study is to determine the effect of diet on anemia symptoms. This study was quantitative with a survey approach, the sample in this study is grade X teenage girls at SMA N 1 Lirik. The sampling technique was total sampling with a sample of 67 people. The data collection technique for this study is a questionnaire. The hypothesis test used is Simple Linear Regression as statistical analysis. The majority of girls' diets are not balanced at 34 people (50.7%) and the majority of women's anemia symptoms are 34 people (50.7%). In this study the results of sig = 0.000 < 0.05, these results it can be concluded that there is an influence on diet on anemia symptoms in grade X teenage girls at SMA N 1 Lirik in 2024.